Antioxidant capacities of the extracts from Perilla frutescens L. leaves using pressurized liquid extraction and conventional techniques - Bao Thy, Vuong; Ngoc Diep, Tran; Chi Dung, Nguyen; Le Dat, Huynh (Vietnam Journal of Biotechnology, 2022)
Perilla frutescens L. is an edible plant used as a food item as well as a folk medicine for human diseases in some Asian countries. Due to limited studies in the extraction of total phenols responsible for its high bio-functional properties, this study is aimed to compare the yields, total phenolic content (TPC), and antioxidant capacities of the extracts between pressurized liquid extraction (PLE) at 100°C with or without ultrasonic treatment and conventional extraction techniques. A batch mode of the PLE system was utilized with the use of water and 50% aqueous ethanol as extraction solvents. Hot water extraction at 80°C and soxhlet extraction were employed as conventional techniques. The extraction yields from each technique were determined before their TPC and antioxidant capacities were examined. The results showed that PLE with and without ultrasonic treatment enhanced the extraction process of TPC as compared with conventional ones. Consequently, PLE resulted in higher antioxidant capacities and lipid peroxidation-inhibiting activity than conventional extraction technique (p < 0.05). However, PLE of bioactive components from Perilla frutescens L. leaves with higher thermal treatment should be considered in future studies.